2022
DOI: 10.1101/gr.275695.121
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an unusually high number of de novo mutations in sperm of older men using duplex sequencing

Abstract: De novo mutations (DNMs) are important players in heritable diseases and evolution. Of particular interest are highly recurrent DNMs associated with congenital disorders that have been described as selfish mutations expanding in the male germline, thus becoming more frequent with age. Here, we have adapted duplex sequencing (DS), an ultradeep sequencing method that renders sequence information on both DNA strands; thus, one mutation can be reliably called in millions of sequenced bases. With DS, we examined ∼4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 74 publications
(169 reference statements)
6
24
0
Order By: Relevance
“…For the majority of the donors (63%) we counted mutations for this variant, but almost one-third of the donors had a VAF of 0 (Figure 2C). Overall, the measured frequencies in sperm DNA for the c.1620C>A variant were in accordance with the VAF recently published (Salazar et al, 2022) and reported in Table 2.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For the majority of the donors (63%) we counted mutations for this variant, but almost one-third of the donors had a VAF of 0 (Figure 2C). Overall, the measured frequencies in sperm DNA for the c.1620C>A variant were in accordance with the VAF recently published (Salazar et al, 2022) and reported in Table 2.…”
Section: Resultssupporting
confidence: 90%
“…Five variants were reported in the literature to be associated with a congenital disorder and categorized to be of clinical significance by ClinVar (pathogenic or benign/uncertain). The other three have not been reported so far, yet were found at a higher frequency in sperm DNA (Salazar et al, 2022) and were predicted in silico to have a strong effect on modifying the protein structure (CADD score). In order to assess if the variant resulted in sub-clonal expansions in the male germline, we screened the VAF in two different cell types of the male germline: the spermatogonial stem cells and the differentiated sperm.…”
Section: Discussionmentioning
confidence: 99%
“…UM, PT, BL, and SK samples of four individuals (P10, P28, P51, and P52) were selected for detection of variants by duplex sequencing based on the presence of PIK3CA or TP53 hotspot variants in PT, but not UM tissue, according to standard NGS. The protocols used here are based on the ones described in more detail in Salazar et al 53 .…”
Section: Methodsmentioning
confidence: 99%
“…Size selected genomic DNA was end-repaired and A-tailed using the NEBNext® Ultra™ II End Repair/dA-Tailing Module (New England Biolabs) according to the manufacturer’s instructions followed by adapter ligation with the NEBNext® Ultra™ II Ligation Module (New England Biolabs) following the manufacturer’s instructions. The adapters ligated to the A-tailed DNA were synthesized as previously described (Adapter 2) 53 . The ligation reaction was then purified using 1.2 volumes of Sera-Mag Select beads (Cytiva).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation